HUBUNGAN BAHASA DAN KEBUDAYAAN (PERSPEKTIF SOSIOLINGUISTIK) - Ahmad Mujib (Sunan Kalijaga State Islamic University Yogyakarta, 2009)
The aim of this paper is to describe the relationship between the language and the culture on sociolinguistic perspective. As a perspective, its framework is based on several factors, which is outside of the language itself. It has something to do with the society. The social reality becomes very critical to understand the meaning itself. With this perspective, theories, which have described the relationship between the culture and the language, can be divided into two categories, namely the subordinate relationship and the coordinate relationship theories. The first relationship correlates with the view that the culture is the main system whereas the language is the subsystem. The second kind of the relationship or the coordinative relationship is based on the understanding that the language and the culture are two different systems, which are adopted by human being. The culture is the ruling system of the human interaction, while the language is the system with its function as the mean of carrying the continuity of that interaction.